A225 AGE OF DIAGNOSIS DOES NOT IMPACT LIKELIHOOD OF EXPERIENCING POOR IBD-RELATED OUTCOMES. (26th February 2020) - Piracha, Y; Reza, S; Fadida, M; Chattha, R; Moradshahi, M; Dezfooli, N; Chattha, Z; Sambhi, G; Chauhan, U; Halder, S L; Marshall, J; Narula, N
Abstract: Aims: The relationship between the age of diagnosis of inflammatory bowel disease (IBD) and adverse disease outcomes has not been well defined. This study aims to determine whether an early age of diagnosis is associated with worse disease outcomes. Methods: This was a retrospective study of IBD patients seen at McMaster University Medical Centre, in Hamilton, ON, Canada from 2012 to 2018. Patients were classified as having poor outcomes if they had any of the following: (1) two or more bowel resections since diagnosis; (2) two or more hospitalizations for disease exacerbation since diagnosis; or (3) more than three months of corticosteroid use within 24 months of diagnosis. Prior knowledge in combination with forward selection was used to develop a multivariate logistic regression model and identify predictors of poor IBD outcomes. The variables used in the forward selection model included age at diagnosis (less than vs. greater than 25), smoking status, sex, disease duration, and type of IBD. Results: A total of 617 IBD patients were included in the analysis, of which 356 (57.7%) had Crohn's disease, 234 (37.9%) had ulcerative colitis, and 27 (4.4%) had IBD-U. The median age at diagnosis was 25 (interquartile range (IQR) 17–37). Median disease duration was 16 years (IQR 11–24). A univariate regression analysis indicated that the odds ratio (OR) of poor outcomes was found to be 0.55 (0.38 - 0.79) for those ≥25 years of age compared to to those <25. In the multivariate regression analysis (Table 1), all of disease duration, smoking status, and IBD type were found to have a significant association with having poor outcomes. Each year of disease duration was associated with an increase in odds of poor outcomes (OR 1.06, 95% CI 1.03–1.09). Active smokers had increased odds of poor outcomes compared to past or never smokers (OR 5.01, 95% CI 1.71–14.68). Patients with ulcerative colitis were less likely to experience poor outcomes compared to Crohn's disease patients (OR 0.38, 95% CI 0.24–0.57). Age of diagnosis was no longer found to have a significant association with poor outcomes, once adjusted for other co-variates (OR 0.74, 95% CI 0.47–1.15). Conclusions: Age of diagnosis was not found to have a relationship with occurrence of poor IBD outcomes, after adjustment for co-variates. However, patients with increased disease duration, active smoking status, and Crohn's disease (compared to UC) were found to have increased odds of poor IBD-related outcomes. Funding Agencies: None